Low But Recoverable Markers of Humoral Immune Response to BNT162b2 in Elderly LTCF Residents Five to Seven Months After Two-Dose Vaccination - Delbrück, Marla; Hoehl, Sebastian; Toptan, Tuna; Schenk, Barbara; Grikscheit, Katharina; Metzler, Melinda; Herrmann, Eva; Ciesek, Sandra (Frontiers in Aging, 2022)
The immune response is known to wane after vaccination with BNT162b2, but the role of age, morbidity and body composition is not well understood. We conducted a cross-sectional study in long-term care facilities (LTCFs) for the elderly. All study participants had completed two-dose vaccination with BNT162b2 five to seven months before sample collection. In 298 residents (median age 86 years, range 75 to 101), anti-SARS-CoV-2 rector binding IgG antibody (anti-RBD-IgG) concentrations were low and inversely correlated with age (mean 51.60 BAU/ml). We compared the results to Health Care Workers (HCW) aged 18 to 70 years (n=114, median age: 53 years), who had a higher mean anti-RBD-IgG concentration of 156.99 BAU/ml. Neutralization against the Delta variant was low in both group (9.5% in LTCF residents and 31.6% in HCWs). The Charlson Comorbidity Index was inversely correlated with anti-RBD-IgG, but not the body mass index (BMI). A control group of 14 LTCF residents with known breakthrough infection had significant higher antibody concentrations (mean 3199.65 BAU/mL), and 85.7% had detectable neutralization against the Delta variant. Our results demonstrate low but recoverable markers of immunity in LTCF residents five to seven months after vaccination.